The Impact of the Different Waves of Covid-19 Pandemic in Chile Across Regions; [Covid-19 en Chile: Análisis de Su Impacto por Olas y Regiones] - Vargas-Rona, C; Elorrieta-Lopez, F; Maddaleno-Herrera, M; Villalobos-Dintrans, P; Iturriaga-Jofre, A; Ayala, A (Sociedad Medica de Santiago, 2023)
Background: The effects of COVID-19 in Chile changed over time and among regions. Aim: To identify patterns in the impact and evolution of COVID-19 for each wave generated between 2020 and 2022 at the 16 regions of the country. Material and Methods: Several indicators related to the pandemic, their evolution and their consequences for the health system and the health of the population were calculated. Results: There are differences in the evolution of the infection across the regions of the country, as well as heterogeneity between waves. Specifically, the second wave in Chile was identified as the one with the greatest impact, with a national death rate of 123.5 deaths per 100,000 inhabitants and 66.4% intensive care unit occupancy rate due to COVID-19. Performing a geographic analysis, it was possible to find systematic patterns, for example, between regions with higher immunization rates and lower rates of lethality, such as the cases of Ñuble and Atacama regions. Conclusions: These results emphasize the need to consider regional differences and the temporal context for the elaboration of strategies to the efficient management of a pandemic. © 2023 Sociedad Medica de Santiago. All rights reserved.